High class in his students emotional experiments and vital planning between dependency - Rajabova Zamira Ravshanbekovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract . This article high class in his students emotional experiments and vital planning between​​ complicated dependency​​ analysis does . Modern psychological research this shows that high​​ social to the floor belonging in students​ two kind kind of - promising and suddenly​​ appearance divisive - emotional​​ sadness​​ types there is to be , their​ every one to a fraction fraction to views various effect​​ Research shows .​​ results this shows that he is himself​​​​​​ respect to do feeling this the effect​ to improve service does . Article legal and education​​ in the field experts , as well as teachers​ and psychologists for practical recommendations gives .